The Right to Tax Credit of Insurers: On the subject of the Replenishment of Damaged Goods - Hernández Patiño, Cecilia (2014)
The main purpose of this article is to give a tax approach about the tax credit insurers which is generated as product replenishment of goods in case of accidents, and thus determine whether or not to use the tax credit referred.From the analysis made in respect of the different doctrinal positions which are presented about the controversy to be develop in this article, we can conclude by saying that when insurance companies deliver goods to the insured as a result of claims do nothing that operations that are part of its line of business, and in that sense, being goods that are required to achieve their economic ends is that in any way, our tax authorities should fix the tax credit that would have been generated concept the acquisition of the property that was the subject of insurance, even more if, as we have indicated the economic purpose of VAT is to tax the final consumer of goods and services, and achieve tax neutrality (application of the tax credit).